MENINGKATKAN MOTIVASI DAN HASIL BELAJAR BIOLOGI DENGAN METODE DISCOVERY LEARNING PADA KONSEP KEANEKARAGAMAN HAYATI BAGI PESERTA DIDIK KELAS X IPA 1 SMAN 3 METRO - Rosita, Hepi (LPPM STKIP PGRI Bandar Lampung, 2020)
Learning biology X IPA 1 SMAN 3 Metro motivation is very important by strudetns increased learn og biology. The research of result to increased motivation and learning biology X IPA 1 topic multigenetict by method discovery learning. Research method :observation, document, and interview. Tecnict of data :test and non test. Increased motivation pracyclus score 40,27 and learning 59. Cyclus I motivation increased rates score 77,83%, and learning 76. Cyclus II motivation increased 105,70, and learning rates score 90. Conclusion: the research to increased motivation 37,56% and learn 17%. Cyclus II motivation to increased 27,87% and learning 14%.